Co-Existing Nanoplastics Further Exacerbates the Effects of Triclosan on the Physiological Functions of Human Serum Albumin - Yan Bao; Yaoyao Wang; Hongbin Liu; Jing Lan; Zhicai Li; Wansong Zong; Zongshan Zhao (Life)
The potential health risks posed by the coexistence of nanoplastics (NPs) and triclosan (TCS) have garnered significant attention. However, the effects and underlying mechanisms of NPs and TCS on key functional proteins at the molecular level remain poorly understood. This study reports the effect of polystyrene nanoplastics (PSNPs) on the binding of TCS to human serum albumin (HSA) using multispectral methods and molecular simulation systems. The experimental results show that TCS significantly inhibits HSA esterase activity, with exacerbating inhibition in the presence of PSNPs, which is attributed to the alteration of HSA conformation and microenvironment of the amino acid residues induced by PSNPs. Molecular docking and site marker competitive studies indicate that TCS predominantly binds to site I of subdomain Sudlow II and the presence of PSNPs does not affect the binding sites. Spectra analyses indicate that the quenching mechanism between TCS and HSA belongs to the static quenching type and the presence of PSNPs does not change the fluorescence quenching type. The HSA fluorescence quenching and the conformational alterations induced by TCS are further enhanced in the presence of PSNPs, indicating that PSNPs enhance the binding of TCS to HSA by making TCS more accessible to the binding sites. This study provides valuable information about the toxicity of PSNPs and TCS in case of co-exposure.